Distribution of Genitive Plural Suffixes in Kosovo-Resava Dialect (Cartographic Representation) - Radovanović, Dragana I.; Nikolić, Jovana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper analyses the materials recorded in the regions of the Kosovo-Resava dialect and then used in the relevant monographic studies and dialect related publications with the aim of presenting the inventory and distribution of genitive plural forms. The areal data display contains the plural genitive forms of nouns of all three genders used in the regions where the three sub-dialects of the Kosovo-Resava area are spoken. The map also displays the use of archaic forms in some Kosovo-Resava regions (genitive ≤ locative forms), as well as the influences that other, non-Slavic Balkan languages have on the inflectional system, particularly in the border areas, that is, in the contact zones.